Massive Traumatic Subcutaneous Emphysema - Fernandes, Diana; Pereira, Sara; Guedes, Celeste; Silva, David (Acta Medica, 2020)
74 year-old-man, former smoker, with chronic obstructive pulmonary disease GOLD grade 4, group D, with emphysema component, treated in a pulmonary rehabilitation program, on oxygen therapy and nocturnal bi-level positive airway pressure (BiPAP) ventilation. During the night he had a traumatic rib fracture (5-11th right ribs) but still he used BiPAP ventilation during the sleep. In the morning after he presented with a diffuse and massive emphysema in the face, thorax and abdominal regions. On physical examination, the patient presented with massive swelling and crepitus on palpation. A chest computed tomography (CT) scan confirmed a diffuse subcutaneous emphysema and revealed a mediastinal emphysema and bilateral small pneumothorax. A fast resolution of the emphysema was of paramount importance as the patient was severely agitated due to his inability to open both eyes, and the need to reintroduce BiPAP ventilation as soon as possible. It was placed a fenestrated subcutaneous catheter on left hemithorax and a subcutaneous ostomy on right hemithorax for comparative purpose. It was also performed a confluent centripetal massage towards drainage orifices, with immediate and substantial improvement of emphysema, especially in left hemithorax, and progressive ocular opening. Further emphysema absorption occurred during hospitalization.
Keywords: lidé; oxygenoterapie; počítačová rentgenová tomografie; subkutánní emfyzém; chronická obstrukční plicní nemoc; Mediastinal Emphysema; Rib Fractures; Humans; Oxygen Inhalation Therapy; Continuous Positive Airway Pressure; fraktury žeber; mužské pohlaví; mediastinální emfyzém; Tomography, X-Ray Computed; Male; Aged; Subcutaneous Emphysema; trvalý přetlak v dýchacích cestách; Pulmonary Disease, Chronic Obstructive; senioři